الهلال في القرآن: تسمية الهلال وتطورها عند علماء التفسير المتقدمين والمعاصرين على وجه الموضوعي - Fahmi Fatwa Rosyadi Satria Hamdani; Alhamuddin Alhamuddin; Putra Bagus Mochammad (Universitas Darussalam Gontor, 2016)
A moon (qamar) is one of the heavens rotates the earth whose appearance changes keep pace with the sidereal and synodic movements. The movements provide significant impact on determining the first day of months in Qamariah calendar. Disagreement in determining the first day of months in Qamariah may be caused by differences in comprehending the first visible crescent moon (hilâl). The objective of the research is to provide understanding about the meanings of hilâl in the Qur’an verses and its implication in determining the first day of months in Qamariah. Thematic method in this research is used to gather the Qur’an verses containing the word “qamar” and “ahillah”, and the verses those are related to determination of the first day of months in Qamariah calendar, arrange them into chronological order and deepen the analysis using astronomical approach. The results show that hilâl is a part of phases of the moon appears in the first two or three nights and last of the month. And yet the hilâl that can be a reference in determining the first day of month is the crescent moon phase that first appears after conjuncture. The implication of hilâl meanings in determining the first day of months in qamariah makes a sign for humans to determine their times for prayers and social activities such as beginning and ending fasting of Ramadan, determining time for pilgrimage (ḥajj), determining ‘iddah period for Muslim women, purchase and sale, rental, cropping, and making arrangement or agreement.